2014
DOI: 10.1186/1756-0500-7-624
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors influencing the ownership and utilization of insecticide-treated bed nets among malaria vulnerable groups in the Buea Health District, Cameroon

Abstract: BackgroundMalaria remains a public health problem and the use of insecticide-treated bed nets (ITNs) against it in vulnerable groups (pregnant women and children <5 years) is recommended in Cameroon. This study was aimed at assessing the socio-demographic factors influencing the ownership and utilization of ITNs among vulnerable groups in the Buea Health District (BHD).MethodsIn a cross-sectional survey a questionnaire was administered in households with at least a child <5 years and/pregnant woman in five hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
34
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 22 publications
14
34
5
Order By: Relevance
“…Marital status is important for LLIN use because our data show that being single was associated with a 10.4-fold increase in the odds of using a bed net compared to being married or cohabiting. The findings of the relationship between marital status and LLIN use are in agreement with what was reported in a study conducted from Cameroon [ 33 ]. The reasons for this finding were not explored in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Marital status is important for LLIN use because our data show that being single was associated with a 10.4-fold increase in the odds of using a bed net compared to being married or cohabiting. The findings of the relationship between marital status and LLIN use are in agreement with what was reported in a study conducted from Cameroon [ 33 ]. The reasons for this finding were not explored in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Such beliefs and ignorance about mechanisms of malaria transmission and proper use of the nets were reported in Ethiopia and elsewhere and in Africa, showing the links between an individual’s knowledge and beliefs related to malaria and LLINs (see for example [ 22 , 24 28 ]). Githinji et al [ 29 ] for Kenya, and Berhanu et al [ 7 ] for Ethiopia similarly reported that behavioural dynamics such as low risk perception, saving nets for future use, awareness and negligence accounted for failures in proper use of LLINs.…”
Section: Discussionmentioning
confidence: 96%
“…LLINs’ utilization and care in Adami Tullu district were dependent on a range of factors, notably the local socio-cultural dynamics, residential patterns, distance of households from net distribution centres, and livelihood conditions. Comparable reasons were reported for communities elsewhere in Ethiopia [ 17 , 18 ]; Kenya [ 19 ], Uganda [ 15 ], Rwanda [ 20 ], Nigeria [ 21 ], Mozambique [ 1 ] and Cameron [ 22 ]. All these studies demonstrate that following mass distribution campaigns, behavioural, demographic, environmental, sociocultural and livelihood factors were important in influencing ownership and proper use of LLINs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the best strategies for attaining and maintaining this universal coverage remains uncertain [ 13 ]. Challenges include the need for establishing appropriate algorithms for determining the number of mosquito nets needed for distribution [ 13 ]; promoting proper use and replacement of old and torn nets [ 14 , 15 ]; as well as understanding the local social norms and other determinants that contribute to increased uptake and utilization [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%